Laboratory Monitoring of Antiretroviral Therapy for HIV Infection: Cost-Effectiveness and Budget Impact of Current and Novel Strategies - Ouattara, Eric N. (Clin Infect Dis, 2016)
Background. Optimal laboratory monitoring of antiretroviral therapy (ART) for human immunodeficiency virus (HIV) remains controversial. We evaluated current and novel monitoring strategies in Côte d′Ivoire, West Africa. Methods. We used the Cost-Effectiveness of Preventing AIDS Complications –International model to compare clinical outcomes, cost-effectiveness, and budget impact of 11 ART monitoring strategies varying by type (CD4 and/or viral load [VL]) and frequency. We included “adaptive” strategies (biannual then annual monitoring for patients on ART/suppressed). Mean CD4 count at ART initiation was 154/μL. Laboratory test costs were CD4=$11 and VL=$33. The standard of care (SOC; biannual CD4) was the comparator. We assessed cost-effectiveness relative to Côte d′Ivoire's 2013 per capita GDP ($1500). Results. Discounted life expectancy was 16.69 years for SOC, 16.97 years with VL confirmation of immunologic failure, and 17.25 years for adaptive VL. Mean time on failed first-line ART was 3.7 years for SOC and <0.9 years for all routine/adaptive VL strategies. VL failure confirmation was cost-saving compared with SOC. Adaptive VL had an incremental cost-effectiveness ratio (ICER) of $4100/year of life saved compared with VL confirmation and increased the 5-year budget by $310/patient compared with SOC. Adaptive VL achieved an ICER <1× GDP if second-line ART and VL costs simultaneously decreased to $156 and $13, respectively. Conclusions. VL confirmation of immunologic failure is more effective and less costly than CD4 monitoring in Côte d′Ivoire. Adaptive VL monitoring reduces time on failing ART, is cost-effective, and should become standard in Côte d′Ivoire and similar settings.